Learning Loss: Online Learning Analysis - Ririen, Deci; Daryanes, Febblina (Indonesian Research Journal on Education, 2024)
The aim of this research is to analyze learning loss in Econometrics material during the online learning period. This research is aqualitative descriptive research. The qualitative data analysis used in this research was adopted based on Miles Huberman's qualitative data analysis techniques which include data reduction, data presentation and verification. The research results show that the indicator of Econometrics material that is least understood and the conceptual errors that occur among students is processing data using statistical applications such as SPSS at 66.67%, followed by inferential statistics material at 60.42%. From the results of student learning loss analysis, educators can determine further learning follow-up, such as changing learning methods and using various learning media in order to overcome learning loss.